(untitled) (LACCEI, 2024)
Air pollution is a global problem that has been increasing in recent years due to industrial growth in countries. One of the most harmful air pollutants is particulate matter due to its possible effects on human health and its rapid dispersion over large areas. Therefore, the purpose of this study is to design a prototype system based on the Internet of Things (IoT) to measure environmental pollution, specifically PM10 and PM2.5 particulate matter. The prototype is made up of a Nova PM SDS011 sensor that detects particles, such as dust, dirt, soot and/or smoke in the air a microcontroller that is in charge of controlling the tasks in the system and sending the information to through the Internet to a data visualization platform that stores and displays all the data in real time interactively through tables and graphs. For its validation, the prototype was implemented near a landfill that is exposed to the open sky in the city of Chitré-Herrera-Panama, where a study was carried out to determine the concentration of particle and air quality. The obtained results showed that the prototype is a viable tool for measuring the concentration levels of particulate matter, since during the measurement period interesting patterns were obtained regarding pollution and population behavior. In addition, our analysis also showed that the proposed design is accessible to a large part of the population due to its low cost, which makes it competitive with other commercial products. For all these reasons, our research seeks to provide an efficient and low-cost technological tool to the population to obtain relevant information on the levels of contamination of particulate matter present in the city of Chitre.